Kaufman field guide to advanced birding : understanding what you see and hear - Kaufman, Kenn (Houghton Mifflin Harcourt, 2011)
Presents a resource that examines the basics of each major bird group and the variations of identification, covering such topics as plumage, body shape, songs, bill size, wing structure, and the behavior of each species.